Strategi Pengembangan Kawasan Wisata di Desa Lewaja Kabupaten Enrekang - Muh.Rigan Yusri; Hairuddin Hairuddin; Hamka Hamka; Imam Fadly; Muh. Arifin; Rahmad Rahmad (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
This research explores strategies for developing the Lewaja Natural Tourism Area in Enrekang Regency, which has considerable potential as a leading destination but has not yet been managed effectively. The study aims to examine the current conditions of the site, highlight its opportunities and constraints, and design strategies for sustainable development. A descriptive qualitative approach was employed, utilizing SWOT (Strengths, Weaknesses, Opportunities, Threats) in conjunction with IFAS and EFAS to establish strategic priorities. The results indicate that Lewaja possesses advantages in terms of natural scenery and accessibility, while weaknesses are found in facility provision and managerial aspects. The proposed strategies derived from the SWOT framework emphasize infrastructure improvement, enhancement of supporting amenities, digital-based promotional efforts, community involvement in destination management, and stronger collaboration between governmental bodies and the private sector. Overall, the study concludes that the future development of Lewaja Peak Natural Tourism should align with the principles of sustainable tourism, aiming to increase its attractiveness, raise service standards, and deliver economic value to the local community.